Interaction of the exr and lon Genes in Escherichia coli - Donch, John (1968)
Strains of Escherichia coli carrying the gene lon typically produced excess capsular polysaccharide, and were sensitive to ultraviolet light (UV) irradiation, thymine starvation, and nalidixic acid, forming long filaments after these treatments. Sensitivity was reduced by a number of posttreatments. In the presence of a second UV sensitivity gene, exr, some of these properties were suppressed: long filaments were not formed, the effect of lon on UV and nalidixic acid sensitivity was greatly reduced, and irradiation posttreatments gave an enhancement of survival characteristic of exr rather than lon strains. Production of capsular polysaccharide was not affected by the exr gene.